Find the sum of all the real numbers x satisfying x ⌊ 2 x ⌋ − ⌊ x + 1 ⌋ = 2 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
How did you arrived at x = 2 1
Log in to reply
Since 0 ≤ { x } < 1 only when { x } = 0 and { x } = 2 1 would make 2 { x } in the RHS to be an integer 0 and 1 respectively. Thanks for the question. I have changed the solution a bit.
You have to enter backslash in front of the braces {} to show them on LaTex.
A rather overrated problem. Nice solution by the way Sir.
From Hermite's Identity; ⌊ 2 x ⌋ = ⌊ x ⌋ + ⌊ x + 2 1 ⌋ , we get
⌊ x ⌋ + ⌊ x + 2 1 ⌋ − ⌊ x + 1 ⌋ = 2 x
From ⌊ x ⌋ − ⌊ x + 1 ⌋ = − 1 which is easily proved.
Therefore, ⌊ x + 2 1 ⌋ = 2 x + 1 = 2 ( x + 2 1 ) = 2 ⌊ x + 2 1 ⌋ + 2 { x + 2 1 } .
Which we get ⌊ x + 2 1 ⌋ = − 2 { x + 2 1 } .
Since we get that − 2 < R H S ≤ 0 , therefore, ⌊ x + 2 1 ⌋ = 0 , − 1 .
And from ⌊ x + 2 1 ⌋ = 2 x + 1 , we know that { x } = 0 , 2 1 because L H S is integer.
If ⌊ x + 2 1 ⌋ = 0 we get x = − 2 1 .
If ⌊ x + 2 1 ⌋ = − 1 we get x = − 1 .
My first two steps were similar to Chew-Seong's solution and found that 2x has to be an integer (RHS=LHS).
Then, I also had similar two cases (if 2x is an integer, then it is either odd or even).
Case 1: if 2x is odd, then 2x=2k+1 and x= (2k+1)/2
2k+1-(k+1)=2k+1
k=-1
x=-0.5
Case 2: if 2x is even, 2x=2k and x=k
2k - (k+1) = 2k
k=-1
x=-1
Finally, I determined their sum for the answer: -0.5 + -1 = -1.5.
(And this way, avoided the use of the fractional parts.)
we get that [ 2 x ] − [ x + 1 ] = 2 x let frac(x) denote fractional part of x.we find 2 cases. case 1: f r a c ( x ) < . 5 ⟹ [ 2 x ] = 2 [ x ] , [ x + 1 ] = [ x ] + 1 [ 2 x ] − [ x + 1 ] = 2 x ⟹ [ x ] − 1 = 2 x note that [x] is always an integer, which means [x]-1 is an integer and so is 2x. this implies f r a c ( x ) = . 5 ( rejected since it contradiicts frac(x)<.5) o r 0 [ x ] = x ⟹ x − 1 = 2 x ⟹ x = − 1 case 2: f r a c ( x ) ≥ . 5 ⟹ [ 2 x ] = 2 [ x ] + 1 , [ x + 1 ] = [ x ] + 1 2 [ x ] + 1 − [ x ] − 1 = [ x ] = 2 x using same logic as before,: f r a c ( x ) = . 5 o r 0 ( r e j e c t e d ) [ x ] = x − . 5 ⟹ x − . 5 = 2 x ⟹ x = − . 5 − 1 − . 5 = − 1 . 5
Anyone with graphical approach...I did by this:(/
Problem Loading...
Note Loading...
Set Loading...
x ⌊ 2 x ⌋ − ⌊ x + 1 ⌋ ⇒ ⌊ 2 x ⌋ − ⌊ x + 1 ⌋ 2 ⌊ x ⌋ + ⌊ 2 { x } ⌋ − ⌊ x ⌋ − 1 ⌊ x ⌋ + 1 = 2 = 2 x = 2 ⌊ x ⌋ + 2 { x } 0 ≤ { x } < 1 is the fractional part of x = ⌊ 2 { x } ⌋ − 2 { x }
Since LHS is integral, RHS must also be integral and there are only two cases when 2 { x } in the RHS is an integer.
When { x } = 0 : ⇒ ⌊ x ⌋ + 1 ⌊ x ⌋ ⌊ x ⌋ + { x } ⇒ x = 0 = − 1 = − 1 + 0 = − 1
When { x } = 2 1 : ⇒ ⌊ x ⌋ + 1 ⌊ x ⌋ ⌊ x ⌋ + { x } ⇒ x = 0 = − 1 = − 1 + 2 1 = − 2 1
Therefore the sum of x satisfying the equation is − 1 − 2 1 = − 1 . 5 .